2021
DOI: 10.1519/jsc.0000000000002729
|View full text |Cite
|
Sign up to set email alerts
|

Interlimb Asymmetries: The Need for an Individual Approach to Data Analysis

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
212
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(238 citation statements)
references
References 31 publications
24
212
0
2
Order By: Relevance
“…In men alone, there was a range of 1.9-49.0% between d and Nd shoulders for absolute Ir strength deficits. Such observations mirror recent recommendations by bishop et al [12] for an individual approach to data analysis when investigating inter-limb asymmetries. However, the differences observed between d and Nd in both absolute and relative strength ratios, regardless of sex, support the recommendation that additional resistance training for concentric Er strength of the d and Nd shoulder must be emphasised for university level volleyball players to address shoulder imbalances and asymmetries.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In men alone, there was a range of 1.9-49.0% between d and Nd shoulders for absolute Ir strength deficits. Such observations mirror recent recommendations by bishop et al [12] for an individual approach to data analysis when investigating inter-limb asymmetries. However, the differences observed between d and Nd in both absolute and relative strength ratios, regardless of sex, support the recommendation that additional resistance training for concentric Er strength of the d and Nd shoulder must be emphasised for university level volleyball players to address shoulder imbalances and asymmetries.…”
Section: Discussionsupporting
confidence: 86%
“…As a consequence of the interest in injury risk and occurrence, asymmetries of < 10% have been proposed as the target for when athletes are returning to or currently competing in sport [2,6,7], and both athlete and non-athlete populations who exhibit inter-limb asymmetries greater than 15% have been associated with increased injury incidence and reduced performance when compared with groups who score below this threshold [8][9][10][11]. However, given the subject-specific and experimental test-specific nature of asymmetries [12], caution should be used when applying these thresholds across different experimental tests and cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been an increase in the utilization of maximal strength tests such as the isometric squat (ISQ) and mid-thigh pull (IMTP). 2,4,6,9,12 These assessments have lower skill requirements than traditional iso-inertial testing and therefore may be more advantageous in settings such as large group programs, rehabilitation and when working with athletes of a low training age. 5…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have included the IMTP, 6,9,25 with fewer employing the ISQ. 2,21 Nuzzo et al 21 utilized both assessment modes and showed they were significantly correlated (r = 0.76); however, peak force and RFD were higher in the ISQ. Greater peak force during the ISQ has also been shown for females only, with a trend evident of higher impulse and RFD during the ISQ but these differences were not significant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation